SELEKSI INDUK KAMBING BOERAWA GRADE 1 DAN 2 BERDASARKAN NILAI MOST PROBABLE PRODUCING ABILITY BOBOT ANAK UMUR ENAM BULAN - Yuwanda, Fitri; ,, Sulastri; Hamdani, M. Dima Iqbal (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The aim of this research was to compare MPPA value for 6 months body weight (6 MBW) of 30 heads Boerawa grade 1 (BG1) and 30 heads Boerawa grade 2 (BG2) does and to determine ten heads of the best BG2 does as replacement stock. Research was conducted by survey method at Karya Makmur-1, Karya Makmur-II, and Pelita Karya-III goat farmer groups located at Wonoharjo village, Sumberejo subregency, Tanggamus regency, Lampung province. Sample observed was selected by purposive sampling. Variables observed were 6 MBW of offspring group of BG1 does and BG2 does at the first and second parity. The variables was analysed to know repeatability value and MPPA value for 6 MBW. Repeatability value were estimated by interclass correlation method, MPPA value of BG1 and BG2 was analysed by t student test. Result of this research indicated 6 MBW of offspring group of BG1 does (20.57 Â± 1.12 kg) was not different (P>0.05) with the offspring group of BG2 does (22.70 Â± 1.06 kg), repeatability value of BG1 and BG2 were 0.29 and 0.33, respectively, MPPA value of BG1 (20.57 kg) were not different (P>0,05) with BG2 (22.70 kg). It could be concluded that genetic potency of BG1 does and BG2 does was not different and the best ten BG2 does were JJ2 (MPPA 23.49 kg), DD3 (23.42 kg), LL1 (23.40 kg), JJ1 (23.32 kg), BB3 (23.29 kg), GG1 (23.27 kg), AA1 (23.14 kg), EE2 (23.08 kg), AA2 (2.05 kg), and GG2 (23.05 kg). (Keywords: Boerawa goat, repeatability, Most probable producing ability, interclass correlation).